Intrafractional 3D localization using kilovoltage digital tomosynthesis for sliding-window intensity modulated radiation therapy. (25th August 2015) - Zhang, Pengpeng; Hunt, Margie; Pham, Hai; Tang, Grace; Mageras, Gig
Abstract: To implement novel imaging sequences integrated into intensity modulated radiation therapy (IMRT) and determine 3D positions for intrafractional patient motion monitoring and management. In one method, we converted a static gantry IMRT beam into a series of arcs in which dose index and multileaf collimator positions for all control points were unchanged, but gantry angles were modified to oscillate ±3° around the original angle. Kilovoltage (kV) projections were acquired continuously throughout delivery and reconstructed to provide a series of 6° arc digital tomosynthesis (DTS) images which served to evaluate the in-plane positions of embedded-fiducials/vertebral-body. To obtain out-of-plane positions via triangulation, a 20° gantry rotation with beam hold-off was inserted during delivery to produce a pair of 6° DTS images separated by 14°. In a second method, the gantry remained stationary, but both kV source and detector moved over a 15° longitudinal arc using pitch and translational adjustment of the robotic arms. Evaluation of localization accuracy in an anthropomorphic Rando phantom during simulated intrafractional motion used programmed couch translations from customized scripts. Purpose-built software was used to reconstruct DTS images, register them to reference template images and calculate 3D fiducial positions. No significant dose difference (<0.5%) was found between the original and converted IMRT beams. For a typical hypofractionated spine treatment, 200 single DTS (6° arc) and 10 paired DTS (20° arc) images were acquired for each IMRT beam, providing in-plane and out-of-plane monitoring every 1.6 and 34.5 s, respectively. Mean ± standard deviation error in predicted position was −0.3 ± 0.2 mm, −0.1 ± 0.1 mm in-plane, and 0.2 ± 0.4 mm out-of-plane with rotational gantry, 0.8 ± 0.1 mm, −0.7 ± 0.3 mm in-plane and 1.1 ± 0.1 mm out-of-plane with translational source/detector. Acquiring 3D fiducial positions from kV-DTS during fixed gantry IMRT is technically feasible, and is capable of providing reliable guidance for intrafractional patient motion management.